Cryotherapy and immune checkpoint inhibitor therapy for the treatment of metastatic non-small cell lung cancer - Gediminas Vasiliauskas; Evelina Sabeckytė; Erika Skrodenienė; Lina Poškienė; Skaidrius Miliauskas; Marius Žemaitis (Pulmonologija ir alergologija, 2023)
Lung cancer remains among the most frequently diagnosed and deadliest diseases in the world. While immune checkpoint inhibitors revolutionized the cancer treatment landscape, only a relatively small proportion of patients benefit from this treatment, likely due to the ability of cancer cells to evade or even exclude the immune system from tumors. Cryotherapy offers a possible way to counteract this process by inducing an inflammatory response and helping in cancer neoantigen presentation, increasing the effectiveness of immunotherapy. While preclinical studies seem to support this claim, further investigation is needed to conclude the benefits and risks of cryotherapy in combination with immune checkpoint inhibitors.